THE ROLE OF THE STATE IN CHILD PROTECTION FROM THE PERSPECTIVES OF CONSTITUTIONAL LAW AND ISLAMIC CIVIL LAW - Ihsan Siregar; Faisar Ananda (Hukum tata Negara/Siyasah, 2026)
Child protection holds a strategic position as a fundamental pillar for national survival, where its fulfillment is jointly governed by religious legal frameworks and state law. This study seeks to examine the concept and implementation of child protection through a comparative analysis of Islamic Law and Positive Law applicable in Indonesia, while also identifying points of convergence between the two systems. The research employs a juridical-normative method grounded in library study with a comparative analytical approach. Secondary sources utilized include the Qur'an, Hadith, books of Islamic jurisprudence, Law Number 35 of 2014 on the Amendment to Law Number 23 of 2002 on Child Protection, and other relevant regulations. Research findings indicate that within Islamic Law, child protection (hifzh al-nasl) encompasses the right to life, lineage, sustenance, education, and affection, all of which constitute absolute obligations of parents and society alike. Indonesian Positive Law, meanwhile, views child protection as an integrative shared obligation among parents, families, communities, and the state, which is legally guaranteed through legislation including protection from violence, exploitation, and discrimination. The fundamental point of commonality between the two legal systems lies in the principle of upholding the best interests of the child (the best interests of the child). The internalization of Islamic values into Indonesia's national legal system has demonstrably strengthened both the moral and juridical legitimacy in realizing comprehensive child protection.